The Effect of Audit Committee, Audit Quality and Financial Distress on Earnings Management - Nurmawati Mambuhu; Ridwansyah Ridwansyah; Tri Widyastuti Ningsih; Irwan Moridu; Hermiyetti Hermiyetti (Yayasan Riset dan Pengembangan Intelektual, 2023)
Many companies are starting to dare to go public so that the need for accounting services is also increasing. Accountant services are used to audit the company's financial statements, which later the quality of the audit results can have an impact on the actions the company will take in continuing its business. One condition that is not desired by all companies is financial distress, which is a condition where the company is on the verge of bankruptcy. This study aims to analyze and examine the factor influence of audit committee, audit quality and financial distress on earnings management. The method of research is using the quantitative and regression analysis. The sample is manufacturing companies that consistently publish financial reports for the 2017-2021 period listed on the Indonesia Stock Exchange with a total sample of 12 companies. The sampling technique used a purposive sampling. The data was analyzed with EViews 10 and was carried out by several tests such as classic assumption test, feasibility analysis, panel regression analysis and coefficient of determination test. The results of this study indicate that the audit committee and audit quality have no significant effect on earnings management. Meanwhile, financial distress has a significant effect on earnings management in manufacturing companies for the period 2017-2021. There is also a result which shows that the audit committee, audit quality and financial distress simultaneously influence earnings management. This research provides a practical contribution in minimizing earnings management actions and conceptual contributions to the development of literature on earnings management at a later date.